2010
DOI: 10.1177/1087057110370894
|View full text |Cite
|
Sign up to set email alerts
|

Automated Image Analysis for High-Content Screening and Analysis

Abstract: The field of high-content screening and analysis consists of a set of methodologies for automated discovery in cell biology and drug development using large amounts of image data. In most cases, imaging is carried out by automated microscopes, often assisted by automated liquid handling and cell culture. Image processing, computer vision, and machine learning are used to automatically process high-dimensional image data into meaningful cell biological results. The key is creating automated analysis pipelines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 53 publications
0
83
0
Order By: Relevance
“…With the advent of high-throughput acquisition technologies like tissue microarrays and automated slide scanners, computerized analysis of tissue images is highly desirable, and studies have shown that quantitative software can detect changes in disease states that are missed by visual inspection (7). Methods for analyzing changes in expression and pattern are well established in cultured cells (8), but histological images are typically more difficult to analyze because cellular heterogeneity and the closely packed organization of cells lead to significant cell segmentation challenges. Several projects have been initiated to build workflows that process IHC images (9,10).…”
mentioning
confidence: 99%
“…With the advent of high-throughput acquisition technologies like tissue microarrays and automated slide scanners, computerized analysis of tissue images is highly desirable, and studies have shown that quantitative software can detect changes in disease states that are missed by visual inspection (7). Methods for analyzing changes in expression and pattern are well established in cultured cells (8), but histological images are typically more difficult to analyze because cellular heterogeneity and the closely packed organization of cells lead to significant cell segmentation challenges. Several projects have been initiated to build workflows that process IHC images (9,10).…”
mentioning
confidence: 99%
“…WCA is a critical in vitro anti-cancer screening tool with single cell resolution [12][13][14][15][16] , ideally utilized after traditional target screenings such as CDC and ADCC assays [9][10][11] , and before preclinical animal tests. Currently, primary target screening assays such as CDC or ADCC assays are all performed in a simplified media or a buffer system.…”
Section: Discussionmentioning
confidence: 99%
“…3). To avoid tedious manual adaptations of feature sets for each specific application, multi-purpose feature libraries have been developed, and these cover the needs for most cell biological assays (Jones et al, 2008;Held et al, 2010;Shariff et al, 2010).…”
Section: Feature Extractionmentioning
confidence: 99%